PEMODELAN ARSITEKTUR SISTEM INFORMASI LAYANAN CUSTOMS, IMMIGRATE DAN QUARANTINE (CIQ) DALAM RANGKA MENCAPAI GOOD GOVERNANCE 4.0 - Fransiskus M H Tjiptabudi (Universitas Nusa Cendana, 2020)
One of the Nawa Cita programs established by the government is to develop Indonesia from the periphery by strengthening human resources, infrastructure and services to be the basis of the government's commitment to develop the East Nusa Tenggara (NTT) region. As a province bordering the Democratic Republic of Timor-Leste, NTT has become a target for the development of border areas, namely the construction of an Integrated Cross-border Post (PLBN) with various supporting facilities. Integrated PLBN is a